Microencapsulation of fatty acid eutectic with polyvinyl chloride shell used for thermal energy storage. (February 2021) - Xing, Jingchen; Zhou, Yucheng; Yang, Keyan; Chang, Jianmin; Yu, Yuxiang; Cai, Liping; Shi, Sheldon Q; Huang, Zhenhua
Highlights: CA-PA eutectic was microencapsulated by PVC using solvent evaporation method. MEPCM with the shell-core ratio of 1:2 had the highest latent heat of 92.13 J/g. Morphology, chemical structure and thermal stability of MEPCM were analyzed. MEPCM had a good thermal reliability after 500 times of thermal cycling. Abstract: MEPCMs have drawn tremendous attention in TES fields. In this study, eutectic of CA and PA was encapsulated by PVC, and the novel MEPCM for TES applications was developed. Microcapsules were prepared by solvent evaporation method and examined using DSC, SEM, LPSA, FTIR, thermal cycling test and TGA. DSC results demonstrated that the phase change temperature of CA-PA eutectic decreased after microencapsulation. The most satisfied sample was the MEPCM with a shell-core ratio of 1:2, which melted at 17.1 °C with the latent heat of 92.1 J/g, the encapsulation ratio was 57.7%. SEM images and LPSA results showed that the prepared MEPCMs were consisted with micro-sized spheres. FTIR results confirmed that the PCM core was successfully encapsulated by the PVC shell, and no chemical reaction was found among the components. The prepared MEPCM showed an excellent thermal reliability after 500 times of thermal cycling. Microencapsulation enhanced the starting temperature of CA-PA eutectic thermal decomposition, and the novel MEPCM exhibited an excellent thermal stability at working temperature from TGA results. Consequently, MEPCM (1:2) was the optimal composition and had great potential for TES applications.